Analisis Kebutuhan Air Bersih di Kota Ternate - Ikbal, Khurniawan; Husain, Thamrin; Altarans, Indra (Peneliti.net, 2025)
Ternate City is a spice city located in North Maluku Province, where geographically the land area of ​​Ternate City is 5,795.40 Km2 which has 7 sub-districts. One of the sub-districts in Ternate City is Pulau Ternate Sub-district with an area of ​​37.24 Km2, Pulau Ternate Sub-district has a population of 8,665 people in 2022 and 8,927 people in 2023. The data shows that the population of Pulau Ternate Sub-district has increased. In addition, with increasing population growth every year and the need for water continues to increase. The imbalance between the amount of clean water and the population in Pulau Ternate Sub-district can result in a lack of water supply for the community, because the availability of clean water sources is limited while population growth continues to increase. This study aims to analyze population growth projections, analyze the calculation of clean water needs, and the availability of clean water in order to be able to serve the community for the next 5 years. The data analysis used in this study included population estimation methods, arithmetic, geometric, and exponential methods. Based on existing data from the Ternate City Water Company (PDAM), the clean water provider in Pulau Ternate District, the current installed capacity is 34.0 L/second, while the planned clean water demand until 2028 is 9.3 L/second. The calculation results indicate a surplus of 24.7 L/second. Therefore, it can be concluded that the current clean water supply is sufficient to meet the clean water needs of the people of Pulau Ternate District until 2028.